The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/molecules28020819
|View full text |Cite
|
Sign up to set email alerts
|

Sweet-Potato-Vine-Based High-Performance Porous Carbon for Methylene Blue Adsorption

Abstract: In this study, sweet-potato-vine-based porous carbon (SPVPC) was prepared using zinc chloride as an activating and pore-forming agent. The optimised SPVPC exhibited abundant porous structures with a high specific surface area of 1397.8 m2 g−1. Moreover, SPVPC exhibited excellent adsorption characteristics for removing methylene blue (MB) from aqueous solutions. The maximum adsorption capacity for MB reached 653.6 mg g−1, and the reusability was satisfactory. The adsorption kinetics and isotherm were in good ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Moreover, an analysis of pore size distributions revealed the presence of abundant microporous and mesoporous structures in both NPC1 and NPC2 (inset of Figure 3a). Combined with the SEM and TEM results, it can be confirmed that the prepared porous carbons possessed rich hierarchical pore structures [6]. In addition, the BET-specific surface areas of NPC2 (1712.7 m 2 g −1 ) were higher than those of NPC1 (1492.9 m 2 g −1 ).…”
Section: Morphology and Structural Characterizations Of N Self-doped ...mentioning
confidence: 59%
See 4 more Smart Citations
“…Moreover, an analysis of pore size distributions revealed the presence of abundant microporous and mesoporous structures in both NPC1 and NPC2 (inset of Figure 3a). Combined with the SEM and TEM results, it can be confirmed that the prepared porous carbons possessed rich hierarchical pore structures [6]. In addition, the BET-specific surface areas of NPC2 (1712.7 m 2 g −1 ) were higher than those of NPC1 (1492.9 m 2 g −1 ).…”
Section: Morphology and Structural Characterizations Of N Self-doped ...mentioning
confidence: 59%
“…As the pH increased from 2 to 12, the q e of NPC1 and NPC2 for MB also increased (Figure 5a). According to the previous report, cationic species were the predominant MB species in solutions [6].…”
Section: Adsorption Performance Of N Self-doped Porous Carbons Toward...mentioning
confidence: 62%
See 3 more Smart Citations